Analisis Sosio Ekonom dalam Mengidentifikasi Perilaku Pencarian Pengobatan Warga Masyarakat Urban Parepare - Gunawan, Syahrul; Nuddin, Andi; Abidin, Abidin (Jurnal Kesehatan Nusantara (JKN), 2025)
Socioeconomic Analysis in Identifying Medical Seeking Behavior in Parepare Urban Community, One of the efforts to achieve public health status is to provide health services. However, the existing service programs are not fully in accordance with the socio-economic factors of the community. In the City of Parepare, among the urban community, which is a community with diverse social and economic behavior, various health service facilities are also found, so it is necessary to study the search for treatment. This study aims to analyze the socio-economic relationship of urban communities in identifying treatment seeking behavior in the City of Parepare. This study was conducted on 98 household heads as a sample. Data was collected using a questionnaire and statistically analyzed using the Chi Square test. The results of the study that knowledge factors (p = 0.449) and attitudes (p = 0.122) did not affect the search for treatment, but the socioeconomic factors of occupation (p = 0.009) and income (p = 0.000) had an effect on seeking treatment for urban communities in ParepareCity. There should be an adjustment between high knowledge and positive attitudes about disease treatment with treatment seeking behavior. so that every community who experiences health problems will try to seek treatment from health services